Analysis of Women's Reproductive and Somatic Health, Hospitalized for Endometrial Hyperplasia and Uterine Bleeding (Eurasian Medical Research Periodical, 2023)
One of the most important problems of modern gynecology is endometrial hyperplastic processes (GPE). GPE is a benign pathology of the endometrium characterized by the progression of clinical manifestations (from simple and complex hyperplasia to atypical precancerous conditions of the endometrium) that occurs against the background of chronic anovulation, when absolute or relative hyperestrogenism occurs in the absence or insufficiency of the antiproliferative effect of progesterone